retagged by
1,145 views

3 Answers

3 votes
3 votes

Let the present ages of Dick, Tom and Harry be $D, T, $ and $ H \; \text{years} $ respectively.

According to the question,

  • $ D = 3T \; \longrightarrow (1) $
  • $ H = 2D \; \longrightarrow (2) $

And, $ D = \left( \frac{D+T+H}{3} \right) – 1 $

$ \Rightarrow D = \left( \frac{D+\frac{D}{3}+2D}{3} \right) – 1 \quad [ \because \text{From equation (1) and (2)}] $

$ \Rightarrow D = \left( \frac{3D+D+6D}{9} \right) – 1 $

$ \Rightarrow 9D = 10D – 9 $

$ \Rightarrow \boxed{D = 9 \; \text{years}} $

Now, Harry present age $H = 2 \times 9 $

$ \Rightarrow H = 18 \; \text{years}.$

Correct Answer $: 18 $

edited by
1 votes
1 votes

Let us assume Tom age is $x$ then:

  • Dick’s age= $3x$
  • Harry’s age=$2.3x=6x$

Now according to the given question, Dick’s age is 1 year less than the average age of all three,

$\therefore 3x=\left (\frac{3x+6x+x}{3} \right )-1$

$\Rightarrow 3x=\left (\frac{10x}{3} \right )-1$

$\Rightarrow 1=\frac{10x}{3}-3x$

$\Rightarrow 1=\frac{10x-9x}{3}$ 

$\Rightarrow 1=\frac{x}{3}$

$\Rightarrow x=3$

So Tom age is $3$ year, 

Harry’s age is $=6x=6*3=18$ year.

$\therefore$ Harry’s age is $18$ year.

 

0 votes
0 votes
Given information:
- Dick is thrice as old as Tom. Let Tom's age be x.
- Harry is twice as old as Dick.
- Dick's age is 1 year less than the average age of all three.

Step 1: Express Dick's age in terms of Tom's age (x).
Dick's age = 3x

Step 2: Express Harry's age in terms of Dick's age.
Harry's age = 2 × Dick's age = 2 × 3x = 6x

Step 3: Set up an equation for Dick's age being 1 year less than the average age of all three.
Dick's age = (Tom's age + Dick's age + Harry's age)/3 - 1
3x = (x + 3x + 6x)/3 - 1
3x = 10x/3 - 1
9x = 10x - 3
x = 3

Step 4: Find Harry's age by substituting x = 3 into the expression for Harry's age.
Harry's age = 6x = 6 × 3 = 18 years

Therefore, Harry's age, in years, is 18.
Answer:

Related questions

1 votes
1 votes
1 answer
1
soujanyareddy13 asked Sep 17, 2021
701 views
If $\text{a,b,c}$ are non-zero and $14^{a} = 36^{b} = 84^{c},$ then $6b \left( \frac{1}{c} \;– \frac{1}{a} \right)$ is equal to
1 votes
1 votes
1 answer
3
0 votes
0 votes
0 answers
4
soujanyareddy13 asked Sep 17, 2021
479 views
How many integers in the set $\{ 100, 101, 102, \dots, 999\}$ have at least one digit repeated $?$
0 votes
0 votes
0 answers
5
soujanyareddy13 asked Sep 17, 2021
348 views
Let $\text{N}, x$ and $y$ be positive integers such that $N = x + y, 2 < x < 10$ and $14 < y < 23.$ If $\text{N} 25,$ then how many distinct values are possible for $\...